Istota i znaczenie barier społeczno-kulturowych w procesie wdrażania controllingu na przykładzie Operatora Gazociągów Przesyłowych Gaz-System SA Oddział we Wrocławiu - Węgrzyn, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper emphasizes the importance of social and cultural conditions of effecting changes in an enterprise. The example of enterprise presented in this paper proves that determination of the Company Director is of particular significance at each change phase. Focusing over time on other aspects connected with the Company management and diverting the Director's attention from the project of controlling implementation weakened the initiatives taken by the Controlling Department and generally reduced the effectiveness of the applied tools within the scope of controlling. In the enterprise, the barriers hindering the implementation of controlling are also driven by emotional and ambitious motives. It was a mistake that the Branch Management had not attempted to solve the conflict among the Managers of the Financial Division as it had thought that such conflict would not affect the work quality and would not be detrimental to the company. The reality showed that as a result of the above mentioned conflict the time had been wasted and many potential opportunities of joint developmental projects execution had been missed. Moreover, in spite of the intra-organization educational process within the scope of controlling that has been functioning continuously since 2001 and despite implementation of many tools useful in the accomplishment of tasks connected with budgeting, controlling is still treated as necessary evil. The author explains the situation by, among other things, the company's monopolistic position in the market which guarantees employees the employment stability and does not force them to engage in the executed tasks or aspire to raise their qualifications as it is in case of market companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 438-445